A duplex endpoint PCR assay for rapid detection and differentiation of Leptospira strains - Benacer, D.; Mohd Zain, S.N.; Lewis, J.W.; Khalid, M.K.N.M.; Thong, Kwai Lin (Sociedade Brasileira de Medicina Tropical (SBMT), 2017)
INTRODUCTION: This study aimed to develop a duplex endpoint PCR assay for rapid detection and differentiation of Leptospira strains.